COMPARATIVE STUDY OF 3D PRINTING PIECES WITH FILAMENT AND POWDER - Caius Stanasel; Traian Buidos; Flaviu Corb; Cosmin Gheghea; Iulian Stanasel (Nonconventional Technologies Review)
This comparative study explores the impact of 3D printing technologies using filament and powder on dimensional accuracy, within the context of Industry 4.0 and rapid prototyping. In an era where efficiency and sustainability are essential, the analysis focuses on how these methods contribute to additive manufacturing processes, facilitating the rapid development of functional prototypes. The use of 3D scanners for precise measurements allows for the evaluation of part quality, highlighting the advantages of each technology in adapting to modern industrial requirements. The study emphasizes the importance of selecting the appropriate printing technology based on project specifications, thereby promoting not only innovation but also a reduced ecological impact through optimized material and resource utilization. This research contributes to a better understanding of the role of 3D printing in transforming industrial processes and supporting a circular economy.